2016
DOI: 10.1074/jbc.m116.721142
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Propanediol Dehydration in Roseburia inulinivorans

Abstract: Glycyl radical enzymes (GREs) represent a diverse superfamily of enzymes that utilize a radical mechanism to catalyze difficult, but often essential, chemical reactions. In this work we present the first biochemical and structural data for a GRE-type diol dehydratase from the organism Roseburia inulinivorans (RiDD). Despite high sequence (48% identity) and structural similarity to the GRE-type glycerol dehydratase from Clostridium butyricum, we demonstrate that the RiDD is in fact a diol dehydratase. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Our model and docking agree well with a recently reported crystal structure of PD bound to ( S )-1,2-propanediol (root-mean-square deviation of 0.56 Å) (Fig. S9) (39). Site-directed mutagenesis experiments confirmed that these four residues are critical for activity (Fig.…”
Section: Characterization Of Cluster 16 Reveals a Ubiquitous Dehydratsupporting
confidence: 90%
“…Our model and docking agree well with a recently reported crystal structure of PD bound to ( S )-1,2-propanediol (root-mean-square deviation of 0.56 Å) (Fig. S9) (39). Site-directed mutagenesis experiments confirmed that these four residues are critical for activity (Fig.…”
Section: Characterization Of Cluster 16 Reveals a Ubiquitous Dehydratsupporting
confidence: 90%
“…The latter is used by a lactaldehyde reductase to produce 1,2-propanediol. This led to the assumption that the GRE of GRM5 was a 1,2-propanediol dehydratase, which was later experimentally verified 90 . This activity was then also proposed for the GREs that are associated with the GRM3 and GRM4; phylogenetic analyses showed that the GREs of GRM3 and GRM4 cluster closely together with the GREs of GRM5 in a maximum-likelihood tree [G] 8 .…”
Section: The Functional Diversity Of Bmcsmentioning
confidence: 99%
“…Currently, this family consists of glycerol dehydratase (GDH) (O’Brien et al , 2004), propane-1,2-diol dehydratase (PDH) (LaMattina et al , 2016), and choline trimethylamine-lyase (CutC) (Craciun and Balskus, 2012). …”
Section: Biochemical and Structural Characterization Of The Glycyl Ramentioning
confidence: 99%
“…This enzyme shares 48% sequence identity with GDH, but preferentially catalyzes the conversion of propane-1,2-diol into propanal (LaMattina et al , 2016) (Fig. 1).…”
Section: Biochemical and Structural Characterization Of The Glycyl Ramentioning
confidence: 99%
See 1 more Smart Citation